ASSESSMENT OF SUSTAINABLE FORESTRY DEVELOPMENT CASE HA TINH PROVINCE - Thi Phuong Nhung, Vo (Journal of Forestry Science and Technology, 2019)
Sustainable development of forestry (SDF) is one of the goals in the general sustainable development of Vietnam. Measuring exactly the level of SDF is necessary, which will be a crucial basis to propose effective solutions for achieving SDF. Based on research results have been published and the possibility of calculation and collection data, the study proposed: i) The set for measuring the sustainable level of Forestry development including 30 indicators in three dimensions: economy (10 indicators), society (11 indicators), and environment (9 indicators); ii) The methods of calculation, normalization, aggregation, and assessment standards used for measuring the sustainable level of Forestry development. The hypothesis of the research was applied in Ha Tinh province in 2017. The application results of the proposition showed that Forestry development in Ha Tinh province was unsustainable and There was an imbalance among 3 pillar components; it also had imbalances among the particulars indicators in each dimension. This will be an important basis to propose a solution for sustainable development in Ha Tinh province. These were the important bases to propose solutions for achieving SDF in Ha Tinh province. The results showed that the given set and the synthetic method and assessment method can be able widely applied.